CEO selection as risk‐taking: A new vantage on the debate about the consequences of insiders versus outsiders - Quigley, Timothy J.; Hambrick, Donald C.; Misangyi, Vilmos F.; Rizzi, G. Alessandra (Strategic Management Journal, 2019)
Abstract Research Summary Our paper sheds new light on the performance implications associated with insider versus outsider CEOs. We frame CEO selection as risk‐taking, in which outsiders are relatively risky hires, with a greater tendency to generate extreme performance outcomes—either positive or negative—as compared to insiders. We base this expectation on two complementary theoretical perspectives: human capital and information asymmetry. We conduct multiple tests on large samples of CEO successions, with controls for endogeneity, and find that outsiders are indeed associated with more extreme performance outcomes than are insiders. Managerial Summary We shed new light on the performance implications associated with outsider CEOs. Instead of asking the customary question, “Do outsider CEOs, on average, perform better or worse than insider CEOs?,” we frame CEO selection as risk‐taking. Under this view, outsiders are relatively risky hires, with a greater likelihood of generating extreme performance outcomes—either positive or negative—as compared to insiders. We conduct multiple tests on large samples of CEO successions and find that outsiders are indeed associated with more extreme performance outcomes than are insiders.